2017
DOI: 10.1080/0284186x.2017.1315173
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and prognostic factors associated with soft tissue sarcoma response to chemotherapy: a subgroup analysis of the European Organisation for Research and Treatment of Cancer 62012 study

Abstract: Prospective central pathology review of tumor histology should be integrated into future STS clinical trials. Doxorubicin-ifosfamide may be most appropriate for young, fit patients with poorly differentiated Grade III tumors including UPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 21 publications
1
28
0
3
Order By: Relevance
“…This practice is based on the subgroup analysis of the phase 3 EORTC 62012 randomized trial, which compared doxorubicin alone versus doxorubicin plus ifosfamide as first‐line treatment in advanced‐stage or metastatic STS. The results demonstrated that liposarcoma had a better tumor response to chemotherapy compared with other histiotypes 202 . Several other studies have further supported the use of doxorubicin‐based therapy, particularly in patients with MLS/RCLS 108,203 …”
Section: Update On Therapy In the Advanced Stagementioning
confidence: 81%
“…This practice is based on the subgroup analysis of the phase 3 EORTC 62012 randomized trial, which compared doxorubicin alone versus doxorubicin plus ifosfamide as first‐line treatment in advanced‐stage or metastatic STS. The results demonstrated that liposarcoma had a better tumor response to chemotherapy compared with other histiotypes 202 . Several other studies have further supported the use of doxorubicin‐based therapy, particularly in patients with MLS/RCLS 108,203 …”
Section: Update On Therapy In the Advanced Stagementioning
confidence: 81%
“…34 In the European Organization for Research and Treatment of Cancer (EORTC) 62012 phase III trial, post hoc subgroup analysis indicated no improvement in response rate or overall survival (OS) in patients with LPS treated with combination doxorubicin-ifosfamide compared with doxorubicin alone. 35 LPS-specific efficacy data are currently unavailable for olaratumab, a PDGFRA-targeting monoclonal antibody recently approved in combination with doxorubicin for untreated advanced STS on the basis of improved OS compared with doxorubicin alone in a randomized phase II trial 36 . Meanwhile, there is clinical evidence that LPS subtypes have differential sensitivity to other available systemic therapies (Table 2).…”
Section: Current Managementmentioning
confidence: 99%
“…The UPS subtype has been included in almost all clinical trials that led to the approval of second line therapies. Anthracyclines, ifosfamide, gemcitabine and trabectedin are active drugs in this histology but UPS is primarily sensitive to the combination of doxorubicin and ifosfamide (86). Based on a phase II study, the combination of gemcitabine with docetaxel was considered to be active in UPS (83), but later a larger phase III study confirmed that the combination of epirubicin with ifosfamide was more effective (87).…”
Section: Chemotherapy and Targeted Therapy For Metastatic Sts Of The mentioning
confidence: 99%